Handbook of Child Psychology and Developmental Science 2015
DOI: 10.1002/9781118963418.childpsy421
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bioecological Influences

Abstract: Within ecologically based approaches to human development the environment is viewed as a multidimensional and structurally organized system, with person and environment contributions functionally linked and probabilistic in nature. Bronfenbrenner's PPCT (process × person × context × time) theory is used as a conceptual framework to illustrate the implications of an ecological perspective, both for understanding and studying development. Within this framework five major issues are reviewed in this chapter: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 244 publications
0
14
0
1
Order By: Relevance
“…Although the relation between youths’ perceptions of existing sexual norms among peers and their own sexual behaviors has been well established (e.g., van de Bongardt et al, 2015 ), the micro-time processes (e.g., dyadic interactions over the course of seconds, minutes, or hours) (Patterson et al, 2000 ; Wachs, 2015 ) through which youth and their peers might interactively construct such norms remain less well understood. The current study was the first to examine how conversations about sex (and specifically—normativity and deviance) during observed dyadic interactions with same-sex friends were related to adolescents’ and young adults’ individual perceptions of sexual peer norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relation between youths’ perceptions of existing sexual norms among peers and their own sexual behaviors has been well established (e.g., van de Bongardt et al, 2015 ), the micro-time processes (e.g., dyadic interactions over the course of seconds, minutes, or hours) (Patterson et al, 2000 ; Wachs, 2015 ) through which youth and their peers might interactively construct such norms remain less well understood. The current study was the first to examine how conversations about sex (and specifically—normativity and deviance) during observed dyadic interactions with same-sex friends were related to adolescents’ and young adults’ individual perceptions of sexual peer norms.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the importance of distinguishing between a more normative versus a more deviant character of communication between peers comes from a significant body of research on processes of deviancy training (i.e., rule-breaking talk and reinforcement thereof) during peer interactions in micro-time (i.e., over the course of seconds, minutes, or hours) and the link with the development of problem behaviors in macro-time (i.e., across years; Patterson, Dishion, & Yoerger, 2000 ; Wachs, 2015 ). Various studies have shown that the amounts of observed rule-breaking versus normative talk, and the reinforcement thereof, during videotaped interactions between adolescents and their friends was associated with the development of problem behaviors, including antisocial tendencies, aggression and violence, substance use, and risk-taking (e.g., Dishion, Capaldi, Spracklen, & Li, 1995 ; Dishion, Eddy, Haas, Li, & Spracklen, 1997 ; Patterson et al, 2000 ; Piehler & Dishion, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…It addresses key questions about the moderating influence of practices and/or interventions -including the character of a specific effect, on a specific child, at a specific time, under a specific set of contextual conditions-to produce a specific set of competencies, behaviors, performance activities, or growth (Fischer & Rose, 2001;Rose et al, 2013). In a complementary manner, structural analyses and dynamic growth modeling enable the precise examination of source(s) of variation within nonlinear systems of hierarchical complexity, particularly when such methods address intersectionality (Fischer & Kennedy, 1997;Hartelman, van der Maas, & Molenaar, 1998;Singer & Willett, 2003;van Geert, 1991van Geert, , 2003 and do not generalize findings to all human beings or all members of a group (M. Cole, 1996, Fischer & Bidell, 2006Ghavami, Katsiaficas, & Rogers, 2016;Spencer, 2017;Wachs, 2015).…”
Section: Science Of Individualitymentioning
confidence: 99%
“…The microsystem is heterogeneous, and various dimensions of the microsystem are functionally linked. Thus, the child’s home environment has both social and physical components (Wachs, 2015) and the nature of proximal parent-child interactions can vary depending on characteristics of the physical microsystem, such as resources (Bradley, 2015). Distinct microsystems afford children opportunities to experience different activities that alone and in combination foster their development.…”
Section: The Bioecological Perspective On Child Gendermentioning
confidence: 99%